PERANCANGAN APLIKASI BERBASIS WEBSITE SISTEM INFORMASI GEOGRAFIS UNTUK SEBARAN INFORMASI UMKM DI KOTA BANDUNG - Mauluddin, Amras; Fatih, Zidhan Maula; Fadillah, Muhammad Fauzan; Mukti, Muhammad Adriena; Ramadhan, Satria Putra (Journal of Information System, Applied, Management, Accounting and Research, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the regional economy, particularly in Bandung City. However, information regarding the distribution and location of MSMEs is not yet presented in an integrated and easily accessible manner for the public and related parties. This study aims to design and build a web-based Geographic Information System (GIS) application that visualizes the distribution of MSMEs in Bandung City interactively. The system development method used is the Agile method, allowing for a flexible and iterative development process based on user needs. The application is built using web technology utilizing the Leaflet.js library as a digital mapping medium to display location data. The result of this research is a web-based GIS application capable of presenting MSME information in the form of a distribution map. It is expected to assist users in obtaining MSME location information effectively and support decision-making related to MSME development in Bandung City.